AIDS Awareness and Condom Use Among Patients in a High-HIV-Prevalence Area in Rural Northern Anhui, China. (1st August 2010) - Mao, Nai-Ling; Pan, Hai-Feng; Lu, Man-Man; Dai, Se-Ying; Chen, Gui-Mei; Tian, Min; Huang, Zhang-Jun; Ye, Dong-Qing
Abstract : The objective was to assess AIDS awareness and condom use in a rural northern Anhui area with a high HIV prevalence. One hundred two AIDS patients underwent a structured interview using a standard questionnaire. There were 51 female and 51 male patients, whose mean age was 46.27 ± 7.27 years and who had good knowledge of AIDS-related issues. More sexually active patients than those nonactive ones knew it more properly that AIDS was a blood-borne disease (100% vs 94.4%; P = 0.03). Significantly more female patients than male (62.7% vs 47.1%; P = 0.047) knew AIDS is incurable. Self-perceived risk was low, and only 84 respondents regarded the condom use as a common problem in their area. Two independent factors associated with a higher rate of condom use were the AIDS patients' income level and their knowledge about condom use. There was statistically significance between the patients who regularly obtained free condoms and those who did not. The patients who bought condoms on their own initiative had a higher chance of using condoms than those who did not. In conclusion, despite a high level of awareness of HIV/AIDS issues, self-perceived risk was low, condom use was infrequent, and especially men continued to have multiple sexual partners.